Pelatihan Pengembangan Bahan Ajar Multimedia Pembelajaran Interaktif Berbasis Pendekatan Saintifik Menggunakan Metode Blended Learning bagi Guru SMP/MTs Muhammadiyah Palembang - Heru Heru; Refi Elfira Yuliani (Jurnal Pengabdian Pada Masyarakat, 2020)
TRAINING OF MULTIMEDIA TEACHING MATERIALS INTERACTIVE LEARNING BASED ON SCIENCE APPROACH USING BLENDED LEARNING METHOD FOR TEACHERS OF SMP / MTS MUHAMMADIYAH PALEMBANG. One of the uses of ICT in learning is interactive instructional multimedia teaching materials. Interactive learning multimedia is something new for SMP and MTs teachers in Muhammadiyah 1 Palembang, because so far teachers have used ICT in the form of Microsoft PowerPoint software only as a media presentation of subject matter so that it is not possible for students to dig deeper knowledge of teaching materials that have been presented in the form of media presentation. This is not in line with the character of the scientific approach initiated by the government in an effort to improve the quality of learning in the classroom. Efforts to improve the quality of teachers through training activities have been carried out by partners (schools), but always experience problems related to the implementation of teacher training, related to the above problems, community service programs (PKM) provide solutions to improve the ability of teachers in developing instructional multimedia teaching materials interactive scientific approach based on SMP and MTs. Muhammadiyah 1 Palembang is conducting training using the Blended Learning method. The implementation of PKM consists of the following stages: 1) the stage of developing instructional systems; 2) the stage of the training using the blended learning method consisting of face-to-face and online learning by utilizing the Moodle Learning Management System (LMS); 3) Evaluation stage. Based on PKM evaluation results, PKM implementation has generally reached an indicator of success, because 87% or around 26 trainees have a value above 75 (an indicator of training success).